Hypergraph‐driven mitigation of cyberattacks. Issue 3 (10th April 2018) - Gonzalez‐Granadillo, Gustavo; Doynikova, Elena; Kotenko, Igor; Garcia‐Alfaro, Joaquin
Abstract : We extend a mitigation model that evaluates individual and combined countermeasures against multistep cyberattack scenarios. The goal is to anticipate the actions of an attacker that wants to disrupt a given system (eg, an information system). The process is driven by a hypergraph formalism, enforced with a stateful return on response investment metric that optimally evaluates, ranks, and selects appropriate countermeasures to handle ongoing and potential attacks.